A synthetic map of the climatopes of the Serra da Estrela (Portugal) - Mora, Carla (2010)
The Serra da Estrela is part of the Iberian Central Cordillera and is the highest mountain in mainland Portugal (40◦ 20’N, 7◦ 35’W, 1993 m a.s.l.). The topoclimates are controlled by the NNE-SSW direction of the mountain range, asymmetric exposure to the prevailing westerly air masses, high relief and irregular morphology. Supported by a network of air temperature data loggers, the influence of the topography on the temperature patterns has been examined. A thorough analysis of climate data from meteorological stations, bibliographical references and the study of the terrain characteristics, including field work, remote sensing and GIS-based digital elevation model analyses, allowed the information to be synthesised in a map of the climatopes at the scale 1:75,000. The climatopes are based on the variation of climatic factors as a result of topography and land cover. Each climatope unit responds similarly to the forcing induced by the atmosphere boundary layer and represents a local climate. The map includes 18 types of climatope and contains a simple, easy-to-understand legend for the non-specialist in climatology, with the possibility for application in land planning.